Desain Pengembangan Kurikulum Madrasah Inklusif Dengan Pendekatan Humanisme Religius - Uswatun Chasanah (STAI Syaichona Moh. Cholil Bangkalan, 2018)
Discrimination in education should be abolished. Every child is entitled to a proper education in accordance with the type of needs and talents of interest as mandated. Through an inclusive madrasah model with its learning model bringing together regular and special needs learners in an educational environment, the educator can realize the values ​​of humanism in the learning process. The manifestation of humanism values ​​can be set forth in the design of inclusive madrasah curriculum development with the approach of religious humanism consisting of four models of curriculum development is duplication model, modification, substitution, and omission. The four curriculum models are described in the Lesson Plan and Individual Learning Program (PPI) designed by internalizing the values ​​of religious humanism through modeling, modeling and habituation activities in the learning process in the classroom or outside the classroom.